Education, ethics of the liberation and community: Comments from the thought of Lev Vygotsky and Paulo Freire - Gómez Torres, Juan Rafael (2019)
This paper raises the need for a debate about the relevance of Vygotsky and Freire for understanding of education as a historical/social community fact; that is, the relationship between formal and non-formal education, the community, in general, as a historical/social and historical/cultural and ethical place, the latter understood it as a link of that community based on an ethics of liberation. The proposed thesis is that, without an epistemologically open link between these dimensions, starting from the two teachers mentioned, education is a task without a future or commitment to the poorest in Latin America.